SOCIALIZATION OF BUMDES FINANCIAL MANAGEMENT TO REALIZE GOOD GOVERNANCE FOR BUMDES WA HYANG TARUMAJAYA - Fatmawati, Faoziah Ulfah; Yuliafitri, Indri; Arum Kanti, Runita (LPPM Univ. Ibn Khaldun Bogor, 2024)
After its ratification and implementation Undang-Undang No. 6 Tahun 2014 tentang Desa, then with the time simultaneously emerged business scale local the village below under the auspices of the Village-Owned Enterprises (BUMDes). In general, the existence of BUMDes is expected to provide donation for improvement source income original village that allows village capable carry out development and improvement people's welfare optimally. However, there is problem base in governance BUMDes is one of them about management finance. Therefore, it is necessary done education for managers BUMDes in the form of seminars and workshops. This activity is carried out with Padjadjaran University students who are members in Work Study Group Real (KKN) for one month in Tarumajaya Village. The topic raised was Literacy Management Finance and Digitalization of Marketing for Manager BUMDes. The implementation of KKN is in the form of making module finance and digital marketing as well as seminars on education management finance and digitalization of marketing. This activity is expected to help increase the understanding of the manager BUMDes about accountability management finance BUMDes and business units so that good governance for BUMDes can be realized.